An interesting case of neonatal aural myiasis in a 13 hours old neonate in a tertiary care hospital - Bharti, Abnish Kumar; Kishore, Jay; Dixit, Aditya (International Journal of Contemporary Pediatrics, 2021)
Myiasis is infestation by fly larvae (diptera) in live vertebrates, including humans. Newborn period is very unusual for any infestation. In literature there are only a few cases reported of neonatal aural myiasis from India. We described a case of aural myiasis caused by the Sarcophagidae family in a 13 hours old newborn in this paper. Aural myiasis in a newborn can be dangerous because of the fatality risk due to penetration to the brain.